Strategic complementarities in a model of commercial media bias - Anna Kerkhof; Johannes Münster (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
Media content is an important privately supplied public good. While it has been shown that contributions to a public good crowd out other contributions in many cases, the issue has not been thoroughly studied for media markets yet. We show that in a standard model of commercial media bias, qualities of media content are strategic complements, whereby investments into quality crowd in further investments and engage competitors in a race to the top. Therefore, Önancially strong public service media can mitigate commercial media bias: the content of commercial media can be more in line with the preferences of the audience and less advertiser-friendly in a dual (mixed public and commercial) media system than in a purely commercial media market.
Keywords: C70; H41; L13; L51; L82; 330; commercial media bias; public service media; advertising; two-sided markets; supermodular games; strategic complements; public goods